Determinants of The China Mutual Funds and Do The Mutual Funds Outperform the Chinese Market - Soo, Tak Wai (2016)
This paper discussed the determinants used for measuring the risk-adjusted performance of the mutual funds in China stock market, such as fund size, transaction fee, fund type and team size and combined them in a single thesis. The funds’ performance is measured using 3 main risk-adjusted performance measurements: Jensen’s Alpha, Treynor’s ratio, Sharpe’s ratio. By using pooled Ordinary Least Squares (OLS) regression, a result is obtained and then further discussed whether the funds have outperformed the Chinese stock market. 40 mutual funds from ShangHai Composite Index have been randomly selected in this thesis for a cross-sectional data analysis. Every data is described and the summaries of the data are listed. After running the regression, the results showed that 3 out of the 4 determinants do not have a significant impact on the performance of the funds. The only determinant that significantly affecting the performance, based on a significance level of 10%, is the size of the team managing the funds. Even then, the human factor (team size) also significantly affected only 2 out of 3 of the performance measurements, namely the Sharpe’s ratio and the Jensen’s Alpha. The size of the team has no impact whatsoever on Treynor’s ratio. This is because Treynor’s ratio excluded the idiosyncratic risk and only measure systematic risk and systematic risk cannot be reduced once the portfolio is well diversified. The 40 funds only outperformed the return of the ShangHai Composite Index if they are measured using Jensen’s Alpha while underperformed using the measurement of Sharpe’s ratio and Treynor’s ratio. The funds’ Sharpe’s ratio is very close to the ShangHai Composite Index’s Sharpe’s ratio, but Treynor’s ratio is way off, having a negative value. We concluded that only human factor can affect the performance of a fund since it is up to the managers on how to pick the stock from the Chinese stock market, and the other factors do not matter, as the law of equilibrium will bring everything (risk and return) back to normal. Since the 3 measurements did not fall into the same ranking, we suspected that the funds either not well diversified enough, or the China market is not efficient. Further study can be made by adding the elements of the human factor, like the sex or age of the managers since human factor is the only determinant that has a significant impact on the funds’ outcome. A deeper depth about China stock market’s efficiency can also be studied to know if the results are affected by the efficiency of the ShangHai Composite Index.